Promotional Effect of Ni−Sn Interaction over Ni Supported on Sn‐incorporated MCM‐41 Catalysts for CO2 Reforming of CH4. Issue 8 (13th May 2021) - Zhao, Yutong; Wang, Zichun; Yang, Wenjie; Gu, Shengshen; Yang, Xiaoxia; Kheradmand, Amanj; Zhang, Xingmo; Luo, Yongming; Huang, Jun; Jiang, Yijiao
Abstract: Sintering of active Ni sites and deposition of coke remain challenging issues for catalytic dry reforming of methane. Herein, Ni supported on the Sn‐incorporated MCM‐41 catalysts were synthesized and tested for DRM process. The structural and physicochemical properties of fresh and spent samples were studied by N2 adsorption‐desorption, XRD, H2 ‐TPR, XPS, TEM, STEM‐EDS, Raman, and TGA techniques. It was revealed that Sn addition improved the dispersion and decreased the size of active Ni nanoparticles by tuning the charger transfer between Ni and Sn. The formation of Ni−SnOx interface provides more possibilities to activate CO2 . The best results were obtained by 2Ni/Sn−MCM‐41 sample with the Ni/Sn mole ratio of 2 : 1, contributing CH4 conversion of 95% and CO2 conversion of 94% at 800 °C. Moreover, the presence of Sn increased the resistance to sintering of Ni‐based catalysts during the severe conditions, thereby the Ni nanoparticle size only appeared a slight growth after 32 h TOS. Combined with the characterization of the spent 2Ni/Sn−MCM‐41 sample, it was revealed that the coke deposition of the deactivated catalyst was dominated by amorphous carbon, which could be responsible for the desirable regeneration ability of the catalyst. Abstract : Nickel‐supported tin‐incorporated catalysts exhibit an enhanced catalytic performance, resulting from the formation of an interfacial structure between Ni and SnOx . Meanwhile, the deactivated catalyst containing less graphitized carbon and smaller nickel nanoparticles offer the possibility for catalyst regeneration.